Next generation of e-learning through the effective usage of cloud computing services - Kurian, Ashly; D Peter Augustine, Dr. (International Journal of Engineering and Technology, 2019)
Cloud Computing is an essential technology intruded in almost all areas where information technology is used. One of the major areas which require Cloud Computing is the Higher Education System where broad and in-depth knowledge and right guidance are highly demanded. Providing such teaching services has also impediments in the traditional education system where cloud computing plays a vital role in a new technology-based educational ecosystem. In this paper, we bring out the advantages of cloud computing to overcome the barriers by providing a new framework of cloud-based e-learning for higher education. Meanwhile, we keep in mind that the use of the system is very much needed for developing countries like India. Using cloud computing in educational institutions can create a common virtual classroom thereby reducing the expenses and the manpower required to install a well-equipped platform. The proposed model facilitates the students and the faculty can access the content 24/7 and also improve the educational performance. This model comes up with cloud system features and with specified cloud services for each purpose. It facilitates the cloud system to perform the services such as PaaS, DBaaS, SaaS, CaaS, and RDaaS for some service components in API. Each of this service has its own functions through the Hy-pervisor.Â Â
Keywords: Cloud System; Cloud-Based E-learning; CaaS; DBaaS; SaaS; PaaS; RDaaS.